The Information Needs of Chinese Family members of Cancer Patients in the Online Health Community: What and Why?. Issue 3 (May 2021) - Ma, Dan; Zuo, Meiyun; Liu, Liu
Highlights: This study focused on the information needs of Chinese family members of cancer patients in the online health community. Three types of information needs and their related stressful events were investigated. Chinese culture may affect the information needs of family members of cancer patients. Information seeking can be a method to help cope with stressful events. Abstract: Meeting the information needs of cancer patients' family members is critical for improving care quality and family members' well-being. An online health community (OHC) can be an effective channel to provide information support, thus attracting many cancer patients' family members. Several studies have examined the information needs of cancer patients' family members in OHCs. However, most of them only focused on health-related information needs for improving patients' physical well-being and did not consider the context of information seeking. Furthermore, most of these studies were conducted in Western countries; thus, their findings may not be generalizable to Chinese culture that emphasizes family-centered decision-making, protection of family members toward the patients, and collectivism. In this study, we investigated what kinds of information Chinese family members of cancer patients seek in the OHC and why they seek them. Hence, we analyzed 8, 334 messages for information seeking posted by 2, 788 family members in one of the most significant Chinese online cancer communities. Stressful events that trigger information needs were also identified for further studying the context of information needs. Based on qualitative content analysis, we discussed the information needs of cancer patients' family members in the OHC and the potential impacts of Chinese culture on family members' information needs. Furthermore, the results confirmed that information seeking could be a method to help family members of cancer patients cope with stressful events in the journey of cancer.